Expediente e Nominata - REVER, Redação (REVER: Revista de Estudos da Religião, 2020)
Avaliadores desta edição: Ana Carolina Mariani (autônomo, Divinópolis-MG); Ana Paula Rodrigues Cavalcanti (UFPB, João Pessoa-PB); Bruno Araújo Oliveira (ETEC, São Paulo-SP); Caroline Filla Rosaneli (PUC-PR, Curitiba-PR); Celso Luiz Terzetti (autônomo, São José do Rio Preto-SP); Cristiane Schumann Silva Curcio (UFJF, Juiz de Fora-MG); Daniela Cordovil (UEPA, Belém-PA); Eduardo Taborda de Jesus (CEFET-MG, Belo Horizonte-MG); Emmanuel Ifeka Nwora (UCB, Brasília-DF); Everton de Oliveira Maraldi (PUC-SP, São Paulo-SP); Fátima Cristina Costa Fontes (FTBSP, São Paulo-SP); Giancarlo Lucchetti (UFJF, Juiz de Fora-MG); Hartmut August (FF, Curitiba-PR); Ipojucan Dias Campos (UEPA, Belém-PA); Jeverson Rogério Costa Reichow (UNESC, Criciúma-SC); Júlio César Moreno (UNISAL, Lorena-SP); Karin Katekaru (autônoma, Florianópolis-SC); Letícia Oliveira Alminhana (UERGS, Porto Alegre-RS); Luiz Carlos Luz Marques (UNICAP, Recife-PE); Marcelo Saad (autônomo, São Paulo-SP); Marcelo Simão Mercante (autônomo, Florianópolis-SC); Marcio Luiz Fernandes (PUC-PR, Curitiba-PR); Marcus Vinicius Reis (UNIFESSPA, Marabá-PA); Marta Helena de Freitas (UCB, Brasília-DF); Matheus Oliva da Costa (UNINTER, Curitiba-PR); Ricardo Assarice dos Santos (USP, São Paulo-SP); Rosimar Dias (FACC-MT, Várzea Grande-MT); Saulo de Tarso Cerqueira Baptista (UEPA, Belém-PA); Suely Akimi Mizumoto (UNIFESP, São Paulo-SP); Thiago Antonio Avellar de Aquino (UFPB, João Pessoa-PB); Waldney de Souza Rodrigues Costa (UERN, Natal-RN); Wladimir Porreca (UnB, Brasília-DF)